2008
DOI: 10.1051/0004-6361:200809644
|View full text |Cite
|
Sign up to set email alerts
|

Gas flow models in the Milky Way embedded bars

Abstract: Context. The gas distribution and dynamics in the inner Galaxy present many unknowns, such as the origin of the asymmetry of the lv-diagram of the Central Molecular Zone (CMZ). On the other hand, there is recent evidence in the stellar component of the presence of a nuclear bar that may be slightly lopsided. Aims. Our goal is to characterize the nuclear bar observed in 2MASS maps and to study the gas dynamics in the inner Milky Way taking into account this secondary bar. Methods. We have derived a realistic ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
212
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(229 citation statements)
references
References 85 publications
15
212
1
Order By: Relevance
“…Based on the above consideration and finding, Binney et al (1991) showed that a bar-like potential naturally reproduces the noncircular motion by comparing observed and calculated l − v (Galactic longitude -line-of-sight velocity from the Local Standard of Rest; LSR, hereafter) diagrams. The streaming motion driven by the bar potential provides an only viable explanation on the parallelogram, which has been explicitly discussed in literatures (Blitz 1994;Koda & Wada 2002;Rodriguez-Fernandez & Combes 2008;Baba, Saitoh & Wada 2010;Molinari et al 2011).…”
Section: E-mail: Stakeru@nagoya-ujp (Tks)mentioning
confidence: 97%
See 2 more Smart Citations
“…Based on the above consideration and finding, Binney et al (1991) showed that a bar-like potential naturally reproduces the noncircular motion by comparing observed and calculated l − v (Galactic longitude -line-of-sight velocity from the Local Standard of Rest; LSR, hereafter) diagrams. The streaming motion driven by the bar potential provides an only viable explanation on the parallelogram, which has been explicitly discussed in literatures (Blitz 1994;Koda & Wada 2002;Rodriguez-Fernandez & Combes 2008;Baba, Saitoh & Wada 2010;Molinari et al 2011).…”
Section: E-mail: Stakeru@nagoya-ujp (Tks)mentioning
confidence: 97%
“…Rodriguez-Fernandez & Combes (2008) presented the first numerical simulations for the parallelogram. Their Figure 14 shows a simulated parallelogram to be compared to the CMZ, while their result is yet crude at best with no detailed fitting to the gas distribution in the l-v diagram.…”
Section: E-mail: Stakeru@nagoya-ujp (Tks)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5b shows the kinematic distance curve for our case at 30 • Galactic longitude. This works only for the circular orbits in the spiral arms and not the elliptical orbits in the Galactic bar (see Rodríguez-Fernández & Combes 2008;Rodríguez-Fernández 2011).…”
Section: Determination Of the Distance Of W43mentioning
confidence: 99%
“…This region is very luminous with L ∼ 3 × 10 6 L , and it contains sources at different evolutionary stages from a Wolf-Rayet cluster to active young star-forming cores (e.g., Blum et al 1999;Motte et al 2003). Nguyen Luong et al (2011) recently discussed several broad velocity components in that regions and suggested that this whole complex might have formed via converging gas flows due to its special location at the interface of the Galactic bar with the inner Scutum spiral arm (Benjamin et al 2005;López-Corredoira et al 2007;Rodriguez-Fernandez & Combes 2008). Different velocity components were also identified in atomic HI emission and absorption (Liszt et al 1993).…”
Section: Introductionmentioning
confidence: 99%